Islamic Spiritual Leadership: Implementation and Its Influence On Bank Syariah Indonesia - Helmi Muhammad (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2023)
For the advancement of organizational leadership practices, the Islamic spiritual leadership model is critical. Particularly, to bridge the gap between the principles of Islamic teachings and their application, such as in Islamic banking. This study seeks to determine the implementation of Islamic spiritual leadership and its influence on Bank Syariah Indonesia. For the research design, I used exploratory descriptive with a holistic single-case design focus. The selection of informants was carried out using purposive and snowball sampling, while the data were obtained through in-depth interviews. The obtained data were further analyzed using an interactive model which had previously been triangulated. The study results show that the Islamic spiritual leadership model can be applied in Bank Syariah Indonesia with an inclusive cultural approach to facilitate the employee to participate in various activities, inducing their sense of pride. Besides, Islamic spiritual leadership's positive principles inherently inspire people, both internally and externally, which fosters the employees’ sense of community and belonging. These values increase organizational commitment, social sensitivity, and life satisfaction.